Differential interactions of the β‐lactam cloxacillin with human renal organic anion transporters (OATs). (25th February 2020) - Lalanne, Sébastien; Le Vée, Marc; Lemaitre, Florian; Le Corre, Pascal; Verdier, Marie‐Clémence; Fardel, Olivier
Abstract: The β‐lactam penicillin antibiotic cloxacillin (CLX) presents wide inter‐individual pharmacokinetics variability. To better understand its molecular basis, the precise identification of the detoxifying actors involved in CLX disposition and elimination would be useful, notably with respect to renal secretion known to play a notable role in CLX elimination. The present study was consequently designed to analyze the interactions of CLX with the solute carrier transporters organic anion transporter (OAT) 1 and OAT3, implicated in tubular secretion through mediating drug entry at the basolateral pole of renal proximal cells. CLX was first shown to block OAT1 and OAT3 activity in cultured OAT‐overexpressing HEK293 cells. Half maximal inhibitory concentration (IC50 ) value for OAT3 (13 µm ) was however much lower than that for OAT1 (560 µm ); clinical inhibition of OAT activity and drug–drug interactions may consequently be predicted for OAT3, but not OAT1. OAT3, unlike OAT1, was next shown to mediate CLX uptake in OAT‐overexpressing HEK293 cells. Kinetic parameters for this OAT3‐mediated transport of CLX ( K m = 10.7 µm ) were consistent with a possible in vivo saturation of this process for high CLX plasma concentrations. OAT3 is consequently likely to play a pivotal role in renal CLX secretion and consequently in total renal CLX elimination, owing to the low plasma unbound fraction of the antibiotic. OAT3 genetic polymorphisms as well as co‐administered drugs inhibiting in vivo OAT3 activity may therefore be considered as potential sources of CLX pharmacokinetics variability.